A Review of Hemophagocytic Lymphohistiocytosis in Patients With HIV. (11th February 2022) - Tabaja, Hussam; Kanj, Amjad; El Zein, Said; Comba, Isin Yagmur; Chehab, Omar; Mahmood, Maryam
Abstract: We provide an elaborate review of cases published between January 2005 and April 2021 on hemophagocytic lymphohistiocytosis (HLH) in HIV patients. Seventy articles describing 81 adult patients (age ≥19 years) were included. The median age was 40 years, and 78% were males. Only 65% were known to have HIV before presentation. CD4 count was ≥200 cells/mm 3 in 23%, and HIV viral load was <200 copies/mL in 41%. The lack of meticulous reporting of ≥5 of 8 criteria for HLH diagnosis was evident in a third of cases. At least 1 infectious agent—other than HIV—was believed to trigger HLH in 78% of patients. The most common were Epstein-Barr virus (26%), human herpesvirus 8 (21%), and Histoplasma capsulatum (17%). Sixty percent survived. Among those, 93% received treatment for identified secondary trigger(s), while 51% received HLH-directed therapy. There was significant heterogeneity in the treatment regimens used for HLH.